The investigator as an independent subject of criminal prosecution in cases of terrorist crimes - Epihin, Alexander Yurevich; Zaitsev, Oleg Aleksandrovich; Gataullin, Zyufyar Shakirovich; Tatyanina, Larisa Gennadyevna; Mishin, Andrey Viktorovich (Cuestiones Políticas, 2020)
This article aims to study the theory and practice of criminal prosecution of terrorist crimes in the Russian Federation. Most of the scientific work is mainly devoted to the study of criminal law and the criminological aspects of the fight against such criminal activities. It is therefore of particular importance to identify the problems of legal regulation of the investigator's activities in order to prosecute criminal offences and develop proposals for their optimal resolution. Cognitionic methods include: an anthropological, synthesis, statistics, partner, particular, systemic structural, legal modeling. In the Russian federation the prosecutor has judicial supervision in the criminal proceedings. Everything concludes that Federal Law of the Russian Federation No. 87-87-05.06.2007 redistributed control of the criminal proceedings by the investigator of the corporation a series of substantive rights of the chief prosecutor of the investigating body. In this sense, the optimal proportion of departmental control and tax supervision of the investigator, such as the establishment of a reasonable balance of these powers of control and supervision, increases the effectiveness of criminal prosecution of terrorism offences.